ANALYSIS OF THE CAUSES OF DEFECTS IN THE PRODUCTION PROCESS OF PILLOWCASES AND BOLSTERS USING THE FMEA METHOD APPROACH AT UD ARJUNO - Fatkhul Musif; Akhmad Wasiur Rizqi; Elly Ismiyah (Sean Institute, 2023)
In the world of manufacturing industry, it is not far from the name of maintaining and improving the quality of its products because it is the most important part of the production process. Quality is defined as a general characteristic of a product or service that affects its ability to meet needs. UD Arjuno is classified as an SME engaged in the manufacture of pillowcase and bolster products. In this business, the quality control carried out is still not optimal, this is indicated by the presence of a number of defective products found in each production. The purpose of this study is to identify the causes of disability that occur with the largest percentage and causative factors and provide suggestions for improvement. In quality control issues, UD Arjuno needs to use the FMEA analysis method to identify the impact of system or process failures, and reduce or eliminate the chances of failure. The results showed that of the 17 potential failure modes that cause defects in pillowcase products, there are 4 failure modes which are the highest RPN values or tercuritis failures that often occur, namely tilted malls, workers lack control of machines, materials easily eaten by rats and operators are less careful.